THE EFFECTIVENESS OF THE PREFERENCE POLICIES IN THE GHANAIAN PROCUREMENT LAW IN PROMOTING THE LOCAL CONSTRUCTION INDUSTRY - Christopher AMOAH; Winston SHAKANTU (Journal of Construction Project Management and Innovation)
The government of Ghana, in trying to promote local businesses, instituted preferential policies in favour of the locally-owned business in section 60 of the current public procurement law. This study therefore investigates the effectiveness of these preference policies in promoting the local construction industry. The research instrument used for this study is the interview guide made up of tick box and open-ended questions to interview 37 construction firms operating from Accra, Ghana. The Head of Public Affairs Officer of the Ghana Public Procurement Authority was also interviewed. Other sources of data included archival records such as contracts previously awarded and the current public procurement regulations. The findings show that the Preference policies in the public procurement law have not been able to have a significant effect on the award of government contracts to local construction firms. The implication is that the purpose of instituting the preference policies in favour of the local contractors and consultants in the construction industry by the government of Ghana has not materialised as major government projects are still awarded to foreign firms, whilst the local construction firms are engaged as subcontractors on these projects, thereby minimising their opportunities to grow. The research has produced a tender evaluation criterion with improved local content mechanisms that will help promote the growth of the local construction industry. The study provides recommendations to policy makers in the Ghanaian construction industry and proposes that the tender evaluation criteria produced by this study be used in the public procurement system to have the desired effect in promoting the indigenous construction sector